بنەما ئیستاتیکییەکانی شیعر لە کۆمەڵە شیعری (ئەی بەندەری دۆست، ئەی کەشتیی دوژمن)ی (بەختیار عەلی)دا - حسێن, د.هەژا فەقێ سلێمان; ئەحمەد, د.مەریوان حەمەکریم (Sulaimani Journal for Humanities, 2023)
Bakhtyar Ali is a prominent name in modern Kurdish literature and culture. He is a writer whose fame has reached beyond the boundaries of Kurdish world. His works have been translated into many languages. Bakhtyar Ali is best known as a novelist; his novels include various themes and techniques. His poetry has not received the same attention by researchers in Kurdish academic community as compared to his novels. In that regards, this research tends to focus on his poetry collection “Ey Benderi Dost, Ey Keshti Duzhmn” – (O, You Friendly Harbour, You Hostile Ship). It is an attempt at depicting aesthetic principles of poetry in that collection. The aim of the research is to present Bakhtyar Ali’s skills and abilities, as a poet, in using various subjective and objective poetic aesthetics, especially in the above-mentioned collection. Method of the research: descriptive analysis Structure of the research: the research is divided into two chapters. Chapter one is the theoretical part which tackles the term of aesthetics, its principles and its levels. The levels are: outer aesthetic level including language, imagery and music, and inner aesthetic level including sentiments, imagination and thought, and the third is the level of direction and aesthetic harmony between the previous two levels. Chapter two is practicing and appointing the principles and levels of poetic aesthetics in “Ey Benderi Dost, Ey Keshti Duzhmn” – (O, You Friendly Harbour, You Hostile Ship). In the end, the conclusions reached and the resources used are all being stated.
Keywords: Poetry; Aesthetics; Principles of Aesthetics; Contemporary Kurdish Poetry; Bakhtiar Ali